Application Of Murottal Therapy Of The Qur'an Surah Ar-Rahman As A Nursing Intervention In Tn.A With Decreasing Heart Output - ica lisnawati (Health Media, 2021)
Chronic kidney failure is a condition in which the kidneys experience a decrease in the glomerular filtration rate (GFR) which causes the kidneys to be unable to filter metabolic wastes to be removed and cause these metabolic wastes to accumulate in the body. The main trigger factor for kidney disease and kidney failure is an increase in blood pressure or vice versa when kidney function is impaired/kidney failure, blood pressure can also increase. Murottal Al-Qur'an Surah Ar-Rahman therapy is one of the interventions that can be done to reduce high blood pressure. Murottal Al-Qur'an therapy in this paper was carried out 3 times for 3 visits to post hemodialysis clients with a time of 10 minutes per session on clients with chronic kidney failure. The purpose of this paper is the application of the Surah Ar-Rahman Murottal Al-Qur'an Therapy intervention aimed at clients with nursing diagnoses of decreased cardiac output. Where the condition of the client before the nursing intervention experienced dizziness and headaches marked by an increase in blood pressure after hemodialysis, namely blood pressure: 191/83 mmHg, then after the intervention of Murottal Al-Qur'an Surah Ar-Rahman Therapy there was a decrease in blood pressure marked by the condition the client becomes relaxed and calm without any complaints with a final blood pressure measurement of 130/80 mmHg. So it can be concluded that murottal Al-Qur'an Surah Ar-Rahman therapy can reduce the increase in blood pressure in patients with chronic kidney failure post hemodialysis.